Astemizole inhibits cell proliferation in human prostate tumorigenic cells expressing ether í -go-go-1 potassium channels - Bernal-Ramos, Gloria; Hernández-Gallegos, Elisabeth; Vera, Eunice; Chávez-López, María de Guadalupe; Zúñiga-García, Violeta; Sánchez-Pérez, Yesennia; Garrido, Efraín; Camacho, Javier (Cellular and Molecular Biology, 2017)
Prostate cancer (PC) is the main cause of cancer mortality in men worldwide. Therefore, novel treatments for PC are needed. Ether í -go-go-1 (Eag1) potassium channels display oncogenic properties, and have been suggested as early tumor markers and therapeutic targets for different cancers. These channels are overexpressed in many human tumors including PC. Astemizole targets several molecules involved in cancer including Eag1 channels, histamine receptors and ABC transporters. Here we studied Eag1 mRNA expression and protein levels in the non-tumorigenic and non-invasive human prostate RWPE-1 cell line, and in the tumorigenic and highly invasive human prostate WPE1-NB26 cell lines. The effect of astemizole on cell proliferation and apoptosis was also studied. The human prostate cell lines RWPE-1 and WPE1-NB26 were cultured following the provider´s instructions. Eag1 mRNA expression and protein levels were studied by real time RT-PCR and immunocytochemistry, respectively. Cell proliferation and apoptosis were studied by a fluorescence AlamarBlue®  assay and flow cytometry, respectively. No difference in Eag1 mRNA expression was observed between the cell lines. However, high Eag1 protein levels were observed in the invasive WPE1-NB26 cells, in contrast to the weak protein expression in RWPE-1 cells. Accordingly, astemizole decreased cell proliferation at nanomolar concentrations only in the invasive WPE1-NB26 cells.  Our results suggest that astemizole may have clinical relevance for prostate cancer treatment in patients with high Eag1 protein levels.